An Improved Reconstruction of Total Marine Fisheries Catches for the New Hebrides and the Republic of Vanuatu, 1950–2014 - Léopold, Marc; David, Gilbert; Raubani, Jason; Kaltavara, Jeremie; Hood, Lincoln; Zeller, Dirk (Frontiers in Marine Science, 2017)
1. Abstract For many small island nations, fisheries provide residents with both food security and economic stability. However, in order to create effective and sustainable fisheries policies and management that will ensure a growing population can prosper, policy makers need to know what is being fished and how much is fished. Vanuatu, the smallest country in Melanesia, has a declared and claimed Exclusive Economic Zone (EEZ) of over 820,000 km2 and fisheries resources play a large part in the food security and economic stability of this country. This reconstruction of total marine fisheries catch of Vanuatu for 1950 to 2014 faced major data gaps. It showed that the reconstructed total catches of nearly 1.4 million t were 40% higher than the 977,997 t reported by the Food and Agriculture Organization (FAO) on behalf of Vanuatu for the same period. However, if large-scale industrial catches are excluded, the reconstructed small-scale fisheries catches (~ 270,000 t) were over 200% higher than the 114,862 t of reported catch that were assumed to represent the small-scale sector in FAO data. Subsistence catches made up almost 93% of small-scale catches, followed by artisanal and recreational catches with ~7% and less than 1%, respectively. By continuously improving the fisheries data of Vanuatu for both the past and the present, policy makers, stakeholders and fishers can make better decisions that will maintain the benefits of marine fishery resources.